Effect of nonoperative concomitant intraarticular pathologies on the outcome of arthroscopic capsular release for adhesive capsulitis of the shoulder - Fatih Yildiz; Abdulkadir Sari; Anil Pulatkan; Vahdet Ucan; Alauddin Kochai; Kerem Bilsel (Acta Orthopaedica et Traumatologica Turcica)
Objective: The aim of this study was to investigate whether coexistent intraarticular lesions are negative prognostic factors for the results of arthroscopic capsular release in frozen shoulder patients. Methods: Seventy-two patients who met inclusion criteria and underwent arthroscopic capsular release between March 2011 and August 2015 for the frozen shoulder were retrospectively evaluated. The patients were divided into two groups according to existence of concomitant intraarticular pathologies detected during arthroscopy. Preoperative and postoperative functional results were assessed with Constant score and shoulder ranges of motion; and the amount of pain was evaluated using visual analog scale (VAS). Results: Group I consisted of 46 patients (mean age 47.2 years and mean follow-up 26 months) without concomitant shoulder pathologies and group II consisted of 26 patients (mean age 48.6 years and mean follow-up 15 months) with coexistent lesions (SLAP lesions, n = 8; SLAP and partial rupture of the RC, n = 4; SLAP, partial rupture of RC and impingement, n = 10; SLAP and impingement, n = 2; and AC arthritis and impingement, n = 2). Preoperatively, the mean ranges of forward flexion (p = 0.221), abduction (p = 0.065), internal rotation (p = 0.564), Constant (p = 0.148) and VAS (p = 0.365) scores were similar between the groups. After a minimum 12 months of follow-up, all patients significantly improved but no statistically significant difference was detected in the mean ranges of forward flexion (152 vs 150; p = 0.902), abduction (137 vs 129; p = 0.095), external rotation (45 vs 40; p = 0.866), internal rotation (5 vs 5 point; p = 0.474), Constant (82 vs 82.3; p = 0.685) and VAS (1.2 vs 1.2; p = 0.634) scores between the groups. Conclusion: The presence of concomitant shoulder pathologies does not appear to affect the clinical outcomes in patients undergoing arthroscopic capsular release for frozen shoulder. Level of evidence: Level III, Therapeutic study. Keywords: Frozen shoulder, Adhesive capsulitis, SLAP, Rotatory cuff, Concomitant pathologies